IMPLEMENTASI LAYANAN PUBLIK TRANSJAKARTA CARES DALAM MENINGKATKAN AKSESIBILITAS PENYANDANG DISABILITAS DI WILAYAH PROVINSI DKI JAKARTA - Evi Irviani; Hendra Wijayanto (Department of Public Administration, Faculty of Social and Political Science, Universitas, 2020)
Abstract, This study aims to determine the implementation of the Transjakarta Cares public service in increasing the accessibility of persons with disabilities in the DKI Jakarta area. This research uses qualitative research. The results of this study indicate that the implementation of the Transjakarta Cares public service in increasing the accessibility of persons is carried out. As seen in the standard and objective indicators, organizational characteristics, resources, social and economic conditions, attitudes of the implementers and organizational communications that support the implementation of the Transjakarta Cares service. The implementation of the Transjakarta Cares service is supported by good coordination, public support from both the government, the private sector and people with disabilities as service users. In addition, the implementation of this service is also supported by skilled and skilled human resources in providing services. However, the implementation of this service also faces obstacles, namely inadequate facility resources, namely the service car unit. Keywords: Public Service, Transjakarta Cares, Policy Implementation Abstrak, Penelitian ini bertujuan untuk mengetahui implementasi dari layanan publik Transjakarta Cares dalam meningkatkan aksesibilitas penyandang disabilitas di wilayah DKI Jakarta. Penelitian ini menggunakan jenis penelitian kualitatif. Hasil penelitian ini menunjukan bahwa implementasi layanan publik Transjakarta Cares dalam meningkatkan aksesibilitas penyandang dilaksanakan. Sebagaimana terlihat pada indiaktor standar dan tujuan, karakteristik organisasi, sumber daya, kondisi sosial dan ekonomi, sikap para pelaksana serta komunikasi organisasi yang mendukung pelaksanaan implementasi layanan Transjakarta Cares tersebut. Pelaksanaan layanan Transjakarta Cares ini didukung oleh koordinasi yang baik, dukungan publik baik dari pemerinytah, swasta maupun penyandang disabilitas sebagai pengguna layanan. Selain itu pelaksanaan layanan ini juga didukung oleh sumber daya manusia yang terampil dan cekatan dalam memberikan pelayanan. Namun, pegimplementasian layanan ini juga mendapatkan hambatan yakni kurang memadainya sumber daya fasilitas yakni unit mobil pelayanan. Kata Kunci: Layanan Publik, Transjakarta Cares, Implementasi Kebijakan